Autophagy Mediates MMP-2 Expression in Glaucomatous Trabecular Meshwork Cells. (10th September 2022) - Xiao, Yan-Ling; Wang, Xiao-Rui; Ye, Kejing; Chen, Wan-Zhu; Zheng, Bing-Ru; Huang, Yi-Hong; Wu, Yu-Yu
Abstract : Purpose . To investigate the effect of 3-methyladenine (3-MA) and starvation on the expression of matrix metalloproteinase (MMP-2) in patients with primary open-angle glaucoma. Methods . Primary TM cells were cultured and divided into three groups. The control group was treated with a normal medium, the 3-MA group was stimulated with 3-MA, and the starvation group received nutrient depletion by replacing the normal media with Earle's balanced salt solution. Cellular mRNA and protein were measured at different 3-MA concentrations and starvation time periods. The level of autophagy was accessed by monodansylcadaverine fluorescent staining and expression of specific autophagy-related genes, light chain 3 (LC3), and Beclin1. The effects of 3-MA and starvation on cell proliferation were determined with a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide assay kit. The mRNA and protein expression of LC3-II, Beclin1, and MMP-2 were measured by reverse transcription-polymerase chain reaction and western blot, respectively. Results . Compared to the control group, starvation significantly upregulated LC3-II and Beclin1 in TM cells after 3 h of stimulation, which peaked at 6 h and 9 h, respectively. Increased MDC-labeled cells were also observed. Starvation downregulated the expression of MMP-2. On the contrary, 3-MA suppressed the activation of autophagy, as shown by the marked downregulation of LC3-II and Beclin1. The expressions of MMP-2 were higher in the 3-MA group compared to the control group, reaching a peak at a concentration of 5 mM. Conclusion . Autophagy may be involved in the pathogenesis of POAG via regulating the expression of MMP-2 and, subsequently, the deposition of the extracellular matrix.